2023
DOI: 10.1371/journal.pone.0293349
|View full text |Cite
|
Sign up to set email alerts
|

Extended difficulties following the use of psychedelic drugs: A mixed methods study

Jules Evans,
Oliver C. Robinson,
Eirini Ketzitzidou Argyri
et al.

Abstract: Long-term adverse experiences following psychedelic use can persist for weeks, months, or even years, and are relatively unexplored in psychedelic research. Our convergent mixed-method study gained quantitative and qualitative data from 608 participants who reported extended difficulties following psychedelic experiences. Data was gathered on the context of use, the nature and duration of the challenges they experienced (including a written description of these), plus a range of possible risk factors and perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0
3

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 45 publications
0
14
0
3
Order By: Relevance
“…15 There has been little systematic research on negative psychedelic experiences or "bad trips," the definition of which remains unclear. 16 One attempt to characterize bad trips is the Challenging Experience Questionnaire, which outlines 7 dimensions of such experiences: physiological distress, grief, fear, insanity, isolation, death, and paranoia. 15 Consumers of psychedelics describe a host of challenging experiences, including re-exposure to past traumas or exposure to traumatic experiences outside of their awareness; paranoia; and fear of being "stuck" in an altered state.…”
Section: Informed Consent In Papmentioning
confidence: 99%
“…15 There has been little systematic research on negative psychedelic experiences or "bad trips," the definition of which remains unclear. 16 One attempt to characterize bad trips is the Challenging Experience Questionnaire, which outlines 7 dimensions of such experiences: physiological distress, grief, fear, insanity, isolation, death, and paranoia. 15 Consumers of psychedelics describe a host of challenging experiences, including re-exposure to past traumas or exposure to traumatic experiences outside of their awareness; paranoia; and fear of being "stuck" in an altered state.…”
Section: Informed Consent In Papmentioning
confidence: 99%
“…These communities have not only recognised but also systematically implemented comprehensive strategies that integrate mental, physical, and spiritual dimensions in preparation for the psychedelic experience 10 – 13 . These holistic approaches are rooted in a deep understanding that navigating these altered states of consciousness without adequate preparation or guidance can pose significant risks and challenges 9 , 14 , 15 .…”
Section: Introductionmentioning
confidence: 99%
“…Consequently, the majority of contemporary clinical and experimental trials have included a specific clinician-led ‘preparation phase’, consisting of a diverse and non-standardised set of techniques, which are posited to significantly influence the course of the subsequent psychedelic experience 16 , 17 . This preparation is aimed at reducing the likelihood of psychologically distressing acute effects 18 20 and extended difficulties following psychedelic drug use 15 , as well as increasing the likelihood of a potentially therapeutic experience 6 , 21 24 . Although there is a consensus in the current scientific discourse around the importance of adequate psychedelic preparation 6 , 25 , there is a pressing need for more rigorous evaluation of the various approaches, techniques and frameworks used to prepare participants 16 , as well as research specifically dedicated to developing instruments to optimise this process.…”
Section: Introductionmentioning
confidence: 99%
“…The study of naturalistic use is relevant to clinical applications of psychedelics since it provides insights into psychedelic-occasioned psychological change and its contextual conditions. While psychedelic use in uncontrolled settings can cause harm ( Carbonaro et al, 2016 ; Evans et al, 2023 ), epidemiological studies reveal that, quite unlike other drug use, psychedelic use is not positively but rather negatively associated with mental health problems ( Johnson et al, 2019 ). Consistent with this, survey studies among psychedelic users have found evidence for positive psychological effects, including enhanced mental well-being, psychological flexibility, and reduced psychopathology ( Aday et al, 2020 ; Davis et al, 2020 ; Haijen et al, 2018 ; Nayak et al, 2023 ; Wolff et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%